Perfil sociodemográfico e do consumo de substâncias psicoativas dos adolescentes e adultos jovens atendidos no CAPS AD, Feira de Santana/Bahia - Silva, Carolina Carvalho (2009)
The consumption of psychoactive substances (PAS) and its association to illicit acts in precocious ages has become a concern as well as a social and public health problem for all segments of society. Objectives: To describe the psychoactive substance consumption and to analyze the familiar, personal and environmental characteristics between the care of adolescents and young adults under treatment at AD CAPS, in Feira de Santana, Bahia. Method: this is a descriptive study, carried out in two phases: stage I - retrospective analysis of medical reports of the adolescents and young adults who had been treated in the period of 2003-2008, and stage II – prospective analysis of convenience sampling, obtained from this population cared at AD CAPS. The variables of the study have been: social demographics of the family and the youngs; related to the consumption of SPA; related to the intervention. Results: 52.6% of the investigated youngs were 20-24 years old and 42.1% were 15-19 years old; 88.8% were males; the majority had low schooling level for their age and lived with their mother or father. The ones who were 12-14 years old have been taken to the AD CAPS by judicial institutions request (75%), those who were 15-19 years, by request of their relatives, parents and friends (32.9%); the young adults (36.7%) have gone there by spontaneous demand; the psychiatric symptoms have been most frequent among others. The most consumed of PAS have been alcohol, tobacco and marijuana, with high ratios of use in the categories “once in one’s life” and “current consumption”. Positive and significant associations (p < 0,05): among the consumption of alcohol, tobacco and marijuana, beginning the use at the age of 10-14 years old; among the use of tobacco and marijuana, in relation to the consumption standard “20 times or more in less than 30 days”; among the alcohol use, in relation to the consumption of “at least a time in less than 30 days”; between the cocaine consumption and the use of six times or more times in less than 30 days and with amount < of 5 grams; between the consumption of crack and the amount of use from 1 to 5 rocks. Most of the studied youngs have stated that their friends had been a reference to start the consumption of drinks and other PAS; the most personal motivations stated by the youngs have been curiosity, acceptance by the group and self-fullfilment; the main consumption of alchool has been done in bars, dance clubs and night clubs; of tobacco at home; other environments, have been chosen for marijuana, solvent inhalants/, crack and other drugs and the use of cocaine has been done most at popular parties. The most reported consequences have been “to feel well”, physical violence (fight), among others. Conclusions: This research disclosed high rates of the precocious initiation and current consumption of the PAS considered light and tolerated socially, besides those ones considered heavy, such as cocaine and crack, among the youngs cared at the AD CAPS; This study has also provided an analysis of the associations of the consumption of PASs with personal, familiar and environmental factors. These findings can subsidize the elaboration of public politicies and the implementation of specific therapeutical actions, adequated to the local reality; as well as stimulate other studies in this area, so that it is possible for this issue to be under continuous and deep study.